Reappraisal of VEGF in the Pathogenesis of Kawasaki Disease - Chun-Yu Chen; Shih-Hui Huang; Kuang-Jen Chien; Tsung-Jen Lai; Wei-Hsiang Chang; Kai-Sheng Hsieh; Ken-Pen Weng (MDPI AG, 2022)
Vascular endothelial growth factor (VEGF) is an important factor in mediating the inflammation of Kawasaki disease (KD). The literature regarding the relationship between VEGF and KD is sparse. The purpose of this study was to investigate the correlation of VEGF and KD. In a prospective study of 42 Taiwanese KD patients (18.9 ± 12.2 months, M/F 22/20) treated with intravenous immunoglobulin (IVIG), a series of VEGF levels was measured from the acute to convalescent phases. KD patients were classified into two subgroups with (n =20) and without (n = 22) acute coronary artery lesions (CALs). Control samples were obtained from 30 febrile controls (19.1 ± 13.7 months, M/F 13/17). In KD patients, VEGF levels in the pre-IVIG acute phase were significantly higher than those in the subacute and convalescent phases (both p < 0.001). In KD patients with CALs, VEGF levels significantly increased immediately in the post-IVIG phase (p = 0.039), and then significantly decreased in the subacute phase (p = 0.002). KD patients with acute CALs had higher median VEGF levels than those without acute CALs from acute to convalescent phases. In the subacute phase, KD patients with acute CALs had significantly higher VEGF levels (p = 0.022) than those without acute CALs. Our data show that VEGF did not decrease after IVIG treatment, and increased significantly after IVIG treatment in KD patients with acute CALs in acute phase. VEGF might be related to the complications of CALs in KD patients.